2018
DOI: 10.4014/jmb.1710.10034
|View full text |Cite
|
Sign up to set email alerts
|

Scarless Genomic Point Mutation to Construct a Bacillus subtilis Strain Displaying Increased Antibiotic Plipastatin Production

Abstract: Bacillus strains produce various types of antibiotics, and random mutagenesis has traditionally been used to overproduce these natural metabolites. However, this method leads to the accumulation of unwanted mutations in the genome. Here, we rationally designed a single nucleotide substitution in the degU gene to generate a B. subtilis strain displaying increased plipastatin production in a foreign DNA-free manner. The mutant strain (BS1028u) showed improved antifungal activity against Pythium ultimum. Notably,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…The fermentation product was extracted and analyzed by HPLC. The HPLC profile showed that the production of two main components of plipastatin and surfactin, for which the retention time of plipastatin was 8− 22 min and that of surfactin was 28−38 min 34,35 (Figure 2). This was consistent with the previously reported data that plipastatin was in the range of 10−25 min and surfactin was in the range of 30−45 min.…”
Section: Analysis Of Fermentation Products Of the Gene-modified Strainmentioning
confidence: 99%
“…The fermentation product was extracted and analyzed by HPLC. The HPLC profile showed that the production of two main components of plipastatin and surfactin, for which the retention time of plipastatin was 8− 22 min and that of surfactin was 28−38 min 34,35 (Figure 2). This was consistent with the previously reported data that plipastatin was in the range of 10−25 min and surfactin was in the range of 30−45 min.…”
Section: Analysis Of Fermentation Products Of the Gene-modified Strainmentioning
confidence: 99%
“…In fact, DegQ stimulates autophosphorylation of DegS sensor kinase resulting in enhanced phospho-transfer to DegU response regulator [29,35]. As a result, the phosphorylated and activated DegU-P version causes higher expression of ppsABCDE operon and increases the plipastatin production [36]. In this study, repair of degQ expression (strain BMV10) ensured DegU-P activation, which doubled the production of plipastatin compared to parental BMV9 strain (3NA sfp+).…”
Section: Discussionmentioning
confidence: 63%
“…In fact, DegQ stimulates autophosphorylation of DegS sensor kinase resulting in enhanced phosphotransfer to DegU response regulator [29,35]. As a result, the phosphorylated and activated DegU-P version causes higher expression of ppsABCDE operon and increases the plipastatin production [36]. In this study, repair of degQ expression (strain BMV10) ensured DegU-P activation, which doubled the production of plipastatin compared to parental BMV9 strain (3NA sfp +).…”
Section: Discussionmentioning
confidence: 65%